Workshop Kewirausahaan Berbasis Digital Marketing sebagai Peluang Bisnis Pada Ikatan Remaja Masjid (IRM) Kecamatan Labuhan Deli Kabupaten Deli Serdang - Haloho, Elisabeth; LG, Lambas Marisi Tua; Darus, Prabudi; Safrul, Edi; Fardinal, Fardinal (Fakultas Ushuluddin, Adab, dan Dakwah, 2024)
Entrepreneurship is closely related to marketing, which is one of the keys to the success of a business or business that will be run by an entrepreneur, in this case of course, in this modern era, marketing is not only done conventionally (offline) but must also be supported by technology. or science and technology. The aim of this activity is to increase understanding regarding digital marketing-based entrepreneurship and improve skills related to digital marketing-based entrepreneurship. The results of this activity are a) The implementation of community service went smoothly in accordance with the expectations of the team implementing community service, because almost all workshop activities were carried out very well, b) The participants were aware of the importance of digital marketing-based entrepreneurship as a business opportunity, c) The participants' response to this activity was very interactive, where the participants asked many questions to the service team and d) broadened the participants' insight both in theory and practice regarding digital marketing-based entrepreneurship.